Meteorological and dust aerosol conditions over the western Saharan region observed at Fennec Supersite‐2 during the intensive observation period in June 2011. Issue 15 (15th August 2013) - Todd, M. C.; Allen, C. J. T; Bart, M.; Bechir, M.; Bentefouet, J.; Brooks, B. J.; Cavazos‐Guerra, C.; Clovis, T.; Deyane, S.; Dieh, M.; Engelstaedter, S.; Flamant, C.; et al.
Abstract : [1] The climate of the Sahara is relatively poorly observed and understood, leading to errors in forecast model simulations. We describe observations from the Fennec Supersite‐2 (SS2) at Zouerate, Mauritania during the June 2011 Fennec Intensive Observation Period. These provide an improved basis for understanding and evaluating processes, models, and remote sensing. Conditions during June 2011 show a marked distinction between: (i) a "Maritime phase" during the early part of the month when the western sector of the Sahara experienced cool northwesterly maritime flow throughout the lower troposphere with shallow daytime boundary layers, very little dust uplift/transport or cloud cover. (ii) A subsequent "heat low" phase which coincided with a marked and rapid westward shift in the Saharan heat low towards its mid‐summer climatological position and advection of a deep hot, dusty air layer from the central Sahara (the "Saharan residual layer"). This transition affected the entire western‐central Sahara. Dust advected over SS2 was primarily from episodic low‐level jet (LLJ)‐generated emission in the northeasterly flow around surface troughs. Unlike Fennec SS1, SS2 does not often experience cold pools from moist convection and associated dust emissions. The diurnal evolution at SS2 is strongly influenced by the Atlantic inflow (AI), a northwesterly flow of shallow, cool and moist air propagating overnight from coastal West Africa to reach SS2 in the early hours. The AI cools and moistens the western Saharan and weakens the nocturnal LLJ, limiting its dust‐raising potential. We quantify the ventilation and moistening of the western flank of the Sahara by (i) the large‐scale flow and (ii) the regular nocturnal AI and LLJ mesoscale processes. Key Points: First detailed observations from western Sahara sector Intraseasonal shift in Saharan heat low drives meteorological/aerosol conditions Atlantic Inflow interaction with low level jet